2023
DOI: 10.3390/cells12071061
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus Patients with DNASE1L3·Deficiency Have a Distinctive and Specific Genic Circular DNA Profile in Plasma

Abstract: Cell-free (cf) extrachromosomal circular DNA (eccDNA) has a potential clinical application as a biomarker. Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with a complex immunological pathogenesis, associated with autoantibody synthesis. A previous study found that SLE patients with deoxyribonuclease 1-like 3 (DNASE1L3) deficiency exhibit changes in the frequency of short and long eccDNA in plasma compared to controls. Here, using the DifCir method for differential analysis of short-read se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…As its distinct topological structure and enigmatic functions in cells, eccDNA, the "magic" mobile and circular DNA molecule, has attracted increasing research interest in recent years. Although numerous studies suggested its potential role in various physiological and pathological statuses, including tumorigenesis [7,21,26], drug-resistance [16,34], aging [35,36], human reproduction [4,8,9] and immune-response [24,37,38], the detailed molecular role of eccDNA remains to be elucidated. One major hurdle in the area is the lack of a rapid and cost-effective method for eccDNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…As its distinct topological structure and enigmatic functions in cells, eccDNA, the "magic" mobile and circular DNA molecule, has attracted increasing research interest in recent years. Although numerous studies suggested its potential role in various physiological and pathological statuses, including tumorigenesis [7,21,26], drug-resistance [16,34], aging [35,36], human reproduction [4,8,9] and immune-response [24,37,38], the detailed molecular role of eccDNA remains to be elucidated. One major hurdle in the area is the lack of a rapid and cost-effective method for eccDNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping and quantification of produced per gene eccDNAs (PpGCs) was realized as described [ 55 , 56 ]. EccDNA reads were mapped with Circle_Finder [ 38 , 57 ] using as arguments the mm10 built of the mouse genome and a minNonOverlap threshold between two split reads of 10 bp.…”
Section: Methodsmentioning
confidence: 99%
“…We used our method, DifCir, for differential analysis of sequenced purified eccDNA data based on their split read signal [ 55 , 56 ]. We calculated the mean values of the PpGCs for each group of replicates and selected for differentially produced per gene eccDNAs (DPpGCs), whose absolute difference of the means between the two groups was more than a selection threshold θ DPpGC = onefold change (FC) in log 2 scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems make the prediction of eccDNA markers from plasma samples a daunting task. However, the use of DifCir on the circulomics analysis of eccDNAs from Systemic Lupus Erythematosus (SLE) patients with DNASE1L3•deficiency have disclosed a distinctive and specific genic eccDNA profile of these patients [112].…”
Section: The Role Of Computational Biology In Profiling Of Eccdna For...mentioning
confidence: 99%